Application of Reciprocal Teaching Style in Improving Student Lecture Process in Volleyball Course - Dian Pujianto; Bayu Insanistyo (Indonesian Journal of Sport, Health and Physical Education Science, 2023)
This research aims to determine the effectiveness of a reciprocal teaching style in volleyball courses. Reciprocal teaching style is a teaching style by forming groups with one member of the group having an advantage in the material to be given. The type of research that will be carried out is classroom action research. So the results of this research cannot be generalized. The subjects of this research were 3rd semester students, totaling 43 students. The data collection technique uses an observation sheet. The results of this research show that a reciprocal teaching style makes a positive contribution to the student learning process in volleyball courses. These results were obtained after observers and colleagues observed and discussed the results of observations that occurred during the action. From the results of observations before the action was given, there were 37.87% who responded well to the lecture, and after the action was given there was an increase, namely; 63.12% of students are active in lectures. It can be concluded that the reciprocal teaching style contributes to improving the volleyball teaching process.